PELATIHAN KEMAMPUAN E-LEARNING GURU MATEMATIKA DENGAN MENGGUNAKAN MOODLE - Syariful Fahmi; Soffi Widyanesti Priwantoro; Burhanudin Arif Nur Nugroho (IKIP PGRI Bojonegoro, 2018)
ABSTRACTThe ability of teachers to teach influenced by ability in technology in the learning process. E-learning as one form of technology will help teachers in the process of teaching and learning. Therefore the ability of e-learning mastery teachers becomes key words in the activities of e-learning in education. One form of E-learning is moodle. The purpose of this training is to provide skills for teachers of mathematics in developing media-based learning, moodle. Moodle is an application program that can modify a media learning into web forms. This application allows students to enter into the